1999
DOI: 10.1002/(sici)1096-9861(19990726)410:2<178::aid-cne2>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Organization of cortical projections to the medullary subnucleus reticularis dorsalis: A retrograde and anterograde tracing study in the rat

Abstract: The distribution and organization of cortical projections to the subnucleus reticularis dorsalis (SRD), the neighboring cuneate nucleus (Cu), and trigeminal nucleus caudalis (Sp5C) were studied in the rat using microinjections of wheat germ agglutinin‐apo horseradish peroxidase‐gold and Biotin‐Dextran. Cortical cells projecting to the caudal medulla were confined to the contralateral layer V with their descending axons crossing the midline at the level of pyramidal decussation. Cortical afferents to Sp5C origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…To identify targets of the ectopic PLAP or GFP-labeled axons in the midbrain and hindbrain region of Tbr1 −/− ; Fezf2 +/− or Tbr1 −/− ; Golli-τ-GFP mice, we compared the PLAP staining pattern with the expression pattern of choline acetyltransferase (ChAT), a marker of midbrain and hindbrain motor nuclei that are targets of layer 5 corticobulbar projections (Valverde, 1962; Satoh et al, 1983; O'Leary and Koester, 1993; Desbois et al, 1999). We found that ectopic, mutant PLAP projections overlapped with ChAT immunostaining in what appeared to be the pedunculopontine tegmental nucleus (Figure 2K–M).…”
Section: Resultsmentioning
confidence: 99%
“…To identify targets of the ectopic PLAP or GFP-labeled axons in the midbrain and hindbrain region of Tbr1 −/− ; Fezf2 +/− or Tbr1 −/− ; Golli-τ-GFP mice, we compared the PLAP staining pattern with the expression pattern of choline acetyltransferase (ChAT), a marker of midbrain and hindbrain motor nuclei that are targets of layer 5 corticobulbar projections (Valverde, 1962; Satoh et al, 1983; O'Leary and Koester, 1993; Desbois et al, 1999). We found that ectopic, mutant PLAP projections overlapped with ChAT immunostaining in what appeared to be the pedunculopontine tegmental nucleus (Figure 2K–M).…”
Section: Resultsmentioning
confidence: 99%
“…The reticular zone just medial to the spinal nucleus of the trigeminal nerve (SpV) has been shown to be important for the coordination of pain and eye blink reflex pathways (Almeida and Lima, 1997; Almeida et al, 1999; Lima and Almeida, 2002; Leite-Almeida et al, 2006; Smit et al, 2006), and receives direct cortical and spinal input (Desbois et al, 1999). Lmx1b -derived neurons were present within the parvocellular reticular formation and dorsal medullary reticular nucleus (PCRt, MdD, Figures 2B–H).…”
Section: Resultsmentioning
confidence: 99%
“…Neurons within the region containing dorsal Lmx1b , PCRt population have been implicated in facilitating nociceptive behavior (Almeida et al, 1999). These neurons receive ascending innervation from dorsal horn projection neurons as well as descending input from multiple cortical areas (Almeida and Lima, 1997; Desbois et al, 1999). Previously, neurons within the MdD region been implicated in the eye blink reflex as they express cFos after supraorbital nerve stimulation and project to the orbicularis oculi muscle innervating VII motoneurons (Smit et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Within the spinal–supraspinal–spinal loop, not only the PAG but also the subnucleus reticularis dorsalis (SRD) of the medulla appears to be critically important for CPM [57,58]. The SRD not only plays an important part in the processing of ascending nociceptive information from peripheral tissues, but also signals back to dorsal horn neurons of the spinal cord [59]. Furthermore, the SRD appears to receive information from several cortical structures including the prefrontal cortex and anterior cingulate cortex, which might explain the influence of psychological factors on CPM [6062].…”
Section: Endogenous Pain Modulationmentioning
confidence: 99%